A case report of right ventricular compression from a septal haematoma during retrograde coronary intervention to a chronic total occlusion. Issue 3 (13th August 2019) - Doshi, Darshan; Hatem, Raja; Masoumi, Amirali; Karmapaliotis, Dimitri
Abstract: Background: Septal haematomas causing left ventricular or biventricular outflow obstruction are rare but known complications of chronic total occlusion (CTO) percutaneous coronary intervention (PCI) and can be life-threatening. Case summary: In this case, we describe the formation of a septal haematoma during retrograde CTO PCI. The patient was initially managed conservatively but became progressively unstable, for which she underwent coiling of the inflow and outflow of the septal perforator. Despite coiling, she developed near complete right ventricular outflow obstruction (based on echocardiography). She was successfully managed with a percutaneous right ventricle assist device, with subsequent resolution of the outflow obstruction. Discussion: Septal haematomas with resultant outflow obstruction have been uniformly fatal. In our case, the use of a percutaneous right ventricle assist device was life-saving.